Performance improvement of sensors response using piece-wise non-linear (PWL) A/D and pulse-width modulation (PWM) A/D techniques - Tijani, Ismaila; Khan, Sheroz (IIUM Press, 2011)
Sensor generally refers to a device that measures or detects a real world condition or parameter such as temperature,- speed, pressure etc, and converts the condition into an analog or digital representation. Different methods based on varying physical properties are been employed for different parameters